(untitled) (Bangladesh Journal of Botany, 2018)
Effects of nod factors (lipo chitooligosaccharide) on seedling growth of maize under salt stress have been studied. The study was framed with seed priming using lipo chitooligosaccharide (LCO) a nod factor @ 4 ml/kg of seeds and without priming on maize seedling growth which was exposed to different levels of salinity (0, 2, 4, 6, 8 and 10 dS/m). Salinity negatively influenced the seedling growth of maize. However nod factor treated maize seedlings had relatively higher germination percentage, root length, shoot length, reducing sugars and amylase activity. Correlation analysis revealed positive relationships between seedling growth parameters. Thus, seed priming with nod factor (4 ml/kg) improved the resistance to salinity at seedling stage. NaCl concentrations restricted amylase enzyme activity and reducing sugar content in the germinating seeds. Priming of nod factor/LCO mitigated the restricted effects of salinity on amylase activity and reducing sugars.